Initial Public Offerings, Accounting Choices, and Earnings Management* - AHARONY, JOSEPH; LIN, CHAN‐JANE; LOEB, MARTIN P. (Contemporary Accounting Research, 1993)
Abstract. This paper investigates whether entrepreneurs manipulate earnings in the periods prior to taking their firms public through the choice of accounting conventions. The preponderance of evidence, using powerful accrual tests that were able to detect earnings management in other contexts, indicates little, if any, manipulation. To the extent that there is earnings management, the results suggest that this phenomenon is more pronounced among small firms and among firms with large financial leverage and is to a lesser degree related to the quality of the underwriters and auditors employed when going public. Résumé. Les auteurs ont voulu savoir si les entrepreneurs manipulaient les bénéfices dans les exercices précédant un appel public à l'épargne par le truchement du choix des normes et conventions comptables. La prépondérance des preuves recueillies à l'aide des puissantes techniques existantes de sondage des produits et des charges visant à déceler les cas d'≪ accommodation » des bénéfices dans d'autres contextes, révèle une faible manipulation, sinon aucune. Dans la mesure où il y a accommodation des bénéfices, les résultats obtenus donnent à penser que le phénomène est davantage accentué chez les entreprises de petite taille ou dont le levier financier est élevé, et qu'il est relié de façon plus ténue à la qualité des preneurs fermes et des vérificateurs à qui l'entreprise a recours lorsqu'elle fait appel public à l'épargne.